Fails the vertical line test at 2,3 and -1, 3
in return it is not a function
By using distance formula (which is attached below), you can solve this problem:
√(x2-x1)^2+(y2-y1)^2
(5, -1) and (5, 3)
√(5-5)^2+(3-(-1))^2
√0^2+4^2
√0+16
√16
4
The distance between the two points is 4.
Answer:
52
Step-by-step explanation:
6^2= 36
4^2= 16
36+16=52
Answer:
35.225 I believe
Step-by-step explanation:
You can always check on Slader.
Answer: X=-7
Step-by-step explanation:
Using PEMDAS;
Step 1: Distribute the "3" in the part of the equation "3(x-2)"
3x - 6
Step 2: Consider the equation as a whole with the newly part of the equation from step 1, as it is a part of the equation
Therefore, re-written as,
3x - 6 + 48 = -3x
Step 3: Evaluate the re-written equation
Using basic mathematics skills, we can evaluate the following,
3x - 6 + 48 = -3x ➡ -6 + 48 = -6x ➡ 42 = -6x ➡ -7 = x
As shown, the answer is x=-7.